LPS promotes a monocyte phenotype permissive for human cytomegalovirus immediate-early gene expression upon infection but not reactivation from latency - V. G. Kew (Nature Portfolio, 2017)
Abstract Human cytomegalovirus (HCMV) infection of myeloid cells is closely linked with the differentiation status of the cell. Haematopoietic progenitors and CD14+ monocytes are usually non-permissive for lytic gene expression which can lead to the establishment of latent infections. In contrast, differentiation to macrophage or dendritic cell (DC) phenotypes promotes viral reactivation or renders them permissive for lytic infection. The observation that high doses of Lipopolysaccharide (LPS) drove rapid monocyte differentiation in mice led us to investigate the response of human monocytes to HCMV following LPS stimulation in vitro. Here we report that LPS triggers a monocyte phenotype permissiveness for lytic infection directly correlating with LPS concentration. In contrast, addition of LPS directly to latently infected monocytes was not sufficient to trigger viral reactivation which is likely linked with the failure of the monocytes to differentiate to a DC phenotype. Interestingly, we observe that this effect on lytic infection of monocytes is transient, appears to be dependent on COX-2 activation and does not result in a full productive infection. Thus LPS stimulated monocytes are partially permissive lytic gene expression but did not have long term impact on monocyte identity regarding their differentiation and susceptibility for the full lytic cycle of HCMV.